Analisis penerapan Standar Akuntansi Pemerintahan Nomor 02 tentang Laporan Realisasi Anggaran pada Kantor Dinas Sosial Kabupaten Kepulauan Sangihe - Mandiangan, Olivianti Mentari; Tinangon , Jantje Janny; Megi , Olivia Yulieta (Riset Akuntansi dan Portofolio Investasi, 2025)
The purpose of this study is to determine and evaluate the implementation of Government Accounting Standard Number 02 in the Budget Realization Report by the Social Service of Sangihe Islands Regency. This study utilizes both qualitative and quantitative data. Qualitative data refers to non-numerical information collected through focus group discussions, interviews, and observations. Meanwhile, quantitative data consists of measurable information that can be calculated and analyzed on a numerical scale. Since the Social Service does not generate income and does not carry forward SiLPA/SiKPA (surplus or deficit) in budget balance changes, it does not present revenue items in the Budget Realization Report. To further enhance the quality of financial information, human resource and financial management within the Social Service should be improved to ensure the ability to present financial reports in accordance with PSAP Number 02 on Budget Realization Reports and to complete the necessary items in the report.